Histopathology in Periprosthetic Joint Infection: When Will the Morphomolecular Diagnosis Be a Reality? - Bori, G; McNally, M; Athanasou, N (Hindawi Publishing Corporation, 2018)
The presence of a polymorphonuclear neutrophil infiltrate in periprosthetic tissues has been shown to correlate closely with the diagnosis of septic implant failure. The histological criterion considered by the Musculoskeletal Infection Society to be diagnostic of periprosthetic joint infection is "greater than five neutrophils per high-power field in five high-power fields observed from histologic analysis of periprosthetic tissue at ×400 magnification." Surgeons and pathologists should be aware of the qualifications introduced by different authors during the last years in the histological techniques, samples for histological study, cutoffs used for the diagnosis of infection, and types of patients studied. Recently, immunohistochemistry and histochemistry studies have appeared which suggest that the cutoff point of five polymorphonuclear neutrophils in five high-power fields is too high for the diagnosis of many periprosthetic joint infections. Therefore, morphomolecular techniques could help in the future to achieve a more reliable histological diagnosis of periprosthetic joint infection.